Bta-miR-34b inhibits proliferation and promotes apoptosis via the MEK/ERK pathway by targeting MAP2K1 in bovine primary Sertoli cells. (21st September 2020) - Zhang, Linlin; Ma, Tiantian; Tao, Qibing; Tan, Wushuang; Chen, Huatao; Liu, Wei; Lin, Pengfei; Zhou, Dong; Wang, Aihua; Jin, Yaping; Tang, Keqiong
Abstract: Immature Sertoli cell (SC ) proliferation determines the final number of mature SCs and further regulates spermatogenesis. Accumulating evidence demonstrated that microRNAs (miRNA s) play an important role in SC proliferation, differentiation, and apoptosis. However, the effect and molecular mechanism of miRNA on bovine immature SC remain to be poorly understood. In this study, miRNA sequencing of testes collected in mature (24-mo old) and immature (neonatal) bulls was conducted to determine the miRNA expression profiles. MicroRNA-34b was one of the differentially expressed miRNAs and was selected for in-depth functional studies pertaining to SC growth. The results showed that miR-34b mimic transfection in primary Sertoli cells (PSC ) inhibited cell proliferation and induced cell cycle arrested at G2 phase and decreased the expression of cell cycle-related genes such as CCNB1, CDK1, CDC25C, and C-MYC . MicroRNA-34b overexpression also leads to increased cell apoptosis, with proapoptotic genes P53 and BAX upregulated, while antiapoptotic gene BCL2 decreased. However, miR-34b knockdown had the opposite effects. Through a combination of transcriptome sequencing, bioinformatics analysis, dual-luciferase reporter assay, and Western blotting, mitogen-activated protein kinase kinase1 (MAP2K1 ), also known as MEK1, was identified as a target of miR-34b. In addition, PSC proliferation inhibition was mediated by cell cycle arrest and apoptosis with MAP2K1 interference. Overexpression of MAP2K1 effectively reversed the miR-34b-repressed PSC cell growth. Moreover, both miR-34b overexpression and MAP2K1 knockdown decreased the protein levels of P-ERK1/2, while MAP2K1 overexpression showed opposite effects. In summary, data suggest that miR-34b regulates PSC proliferation and apoptosis through the MEK/ERK signaling pathway. These data provide a theoretical and experimental framework for further clarifying the regulation of cell growth in PSC of bovine.